Investigating pluripotency and primordial germ cell development in axolotl with a focus on axnanog and axblimp1 - Redwood, Catherine (2009)
The study of pluripotent cells in mouse has revealed a core transcription factor network. Pluripotent cells have not been identified in many non-mammalian organisms, but cells with pluripotent properties are found in axolotl (Ambystoma mexicanum) a urodele amphibian. Similarities, between the morphological processes in amniotes and those in urodeles led to the suggestion that amniotes may have arisen from a urodele-like ancestor. Thus, studying the pluripotency network in axolotl may be key to understanding the evolution of mechanisms governing pluripotency in amniotes. This study describes the investigation of two of the core pluripotency trancription factors, Axnanog and Axoct4. Coexpression of axnanog and axoct4 was detected in the undifferentiated tissues of blastula and gastrula stage embryos, suggesting a conserved role in pluripotency/multipotency. Antisense morpholino oligonucleotides were employed to investigate the function of these two molecules. Gastrulation was disrupted in Axnanog morphant embryos. Additionally, they maintained expression of genes associated with pluripotency and early lineage specification, but only expressed low levels of terminal differentiation markers. There are two explanations for this phenotype, a cell migration defect or a developmental block. Axoct4 morphant embryos had a similar phenotype suggesting that Axoct4 may function in a common pathway.